2022
DOI: 10.3389/fphar.2021.784281
|View full text |Cite
|
Sign up to set email alerts
|

Ocimum basilicum Essential Oil Modulates Hematotoxicity, Oxidative Stress, DNA Damage, and Cell Cycle Arrest Induced by β-cyfluthrin in Rat Liver

Abstract: Pesticides are used in large quantities infrequently, resulting in environmental damage and health issues. The goal of the current study was to explore the ameliorating effect of Ocimum basilicum (Basil) leaves essential oil versus the harmful effects of β-cyfluthrin in rat liver. Male Wistar rats were classified at random into four groups; negative control (corn oil), basil leaves essential oil (BEO, 3 ml/kg), β-cyfluthrin (positive control) (β-Cyf; 15 mg/kg BW, 1/25 LD50), and BEO plus β-Cyf, respectively. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…O. basilicum essential oil demonstrated a higher content of phenols and maximal levels of DNA protection and free radical scavenging against toxicity induced by cadmium chloride [ 46 ]. As found in other research, the antioxidant property of this plant oil may be due to the polyphenoid rosmarinic acid, which is a derivative of cinnamic acid [ 47 ].…”
Section: Discussionmentioning
confidence: 89%
“…O. basilicum essential oil demonstrated a higher content of phenols and maximal levels of DNA protection and free radical scavenging against toxicity induced by cadmium chloride [ 46 ]. As found in other research, the antioxidant property of this plant oil may be due to the polyphenoid rosmarinic acid, which is a derivative of cinnamic acid [ 47 ].…”
Section: Discussionmentioning
confidence: 89%
“…Pyrethroids have been demonstrated to damage cells via oxidation, and to accumulate peroxidation products, which are employed as indicators of oxidative stress [ 8 , 54 ]. The testes are frequently exposed to low oxygen levels as a result of their constrained vascularity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, pyrethroid pesticides could damage the testis. Some studies have found that cyfluthrin could cause abnormal morphology and death of spermatozoa 9 . Meanwhile, lambda cyhalothrin can also cause the decrease of sperm motility in rats with abnormal testicular morphology 35 .…”
Section: Discussionmentioning
confidence: 99%
“…In the early stage, the research group detected pesticide residues in vegetable greenhouse in the suburbs of this area, and found that the detection rate of cyfluthrin was the highest. Studies have shown that cyfluthrin exposure can cause neurological and reproductive system damage 9–11 . Therefore, the toxicity of cyfluthrin has aroused widespread concern.…”
Section: Introductionmentioning
confidence: 99%